Filaggrin loss‐of‐function mutations as risk factors for ischemic stroke in the general population. (2nd March 2017) - Varbo, A.; Nordestgaard, B. G.; Benn, M.
Abstract : Essentials FLG mutations cause atopic dermatitis, previously found to be associated with ischemic stroke. Association between FLG mutations and ischemic stroke was examined in 97 174 Danish individuals. FLG mutations were associated with increased ischemic stroke risk in the general population. The association was most pronounced in younger individuals, and in current and former smokers. Summary: Background: Heritability studies have shown a considerable genetic component to ischemic stroke risk; however, much is unknown as to which genes are responsible. Also, previous studies have found an association between atopic dermatitis and increased ischemic stroke risk. Objective: To test the hypothesis that FLG loss‐of‐function mutations, known to be associated with atopic dermatitis, were also associated with ischemic stroke. Methods: A total of 97 174 individuals, with 3597 cases of ischemic stroke, from the Copenhagen General Population Study, the Copenhagen City Heart Study and the Copenhagen Carotid Stroke Study were genotyped for the two most common filaggrin mutations, FLG R501X and FLG 2282del4. Results: FLG mutation carriers had an odds ratio for ischemic stroke of 1.15 (95% confidence interval [CI], 1.02–1.30) compared with non‐carriers. Risk of ischemic stroke for FLG mutation carriers was higher among individuals aged < 50 years, with an odds ratio of 1.72 (1.11–2.67), compared with non‐carriers. When stratified for smoking, ischemic stroke risk was primarily seen in current and former smokers, with an odds ratio of 1.25 (1.08–1.44). FLG mutations were not associated with conventional cardiovascular risk factors except for slightly more pack‐years smoked among mutation carriers, but were associated with increased risk of self‐reported eczema, with an odds ratio of 1.42 (1.32–1.52). Finally, self‐reported eczema was associated with increased ischemic stroke risk, with an age and sex adjusted hazard ratio of 1.24 (1.01–1.52); however, the association was not statistically significant after multifactorial adjustment. Conclusion: In this study of 97 174 individuals from the Danish general population, FLG loss‐of‐function mutations were associated with increased ischemic stroke risk; however, residual confounding is a possibility.